Pediatric kidney transplant recipients with and without underlying structural kidney disease have a comparable risk of hospitalization associated with urinary tract infections - Spiwak, Elizabeth; Nailescu, Corina; Schwaderer, Andrew (Frontiers in Pediatrics, 2022)
Introduction: Urinary tract infections (UTIs) are a common and potentially serious kidney transplant complication. Pediatric kidney transplants are potentially at increased risk for UTIs due to higher rates of structural kidney disease as the underlying end stage kidney disease (ESKD) etiologies. The objective of this manuscript is to determine if children with structural kidney disorders are more prone to UTIs post kidney transplant. Methods: Hospitalizations for pediatric kidney transplant recipients were retrospectively reviewed over a 4-year period for UTIs in the diagnostic codes. The patient age, sex, graft age, underlying diagnosis for cause of ESKD, symptoms at presentation, urinalysis results, and urine culture results were recorded. UTI rates, febrile UTI rates and UTI rates in the 1st year post transplant were compared between children with ESKD due to structural versus non-structural kidney disease. Results: Overall 65 of 145 pediatric kidney transplant patients were accounted for 191 hospitalizations for kidney transplant complications over the 4-year study period. UTIs were components of 30% of the hospitalizations. Overall UTI rates, febrile UTI rates, UTI rates for the initial hospitalization, and UTI rates for the 1st year post kidney transplant were comparable for children with versus without structural ESKD etiologies. Conclusions: UTIs are frequent components of hospitalizations for pediatric kidney transplant recipients. Children and with and without structural kidney disease as an ESKD etiology have similar UTI rates indicating that UTI susceptibility is primarily due to the transplant process and/or medication regimens. UTIs represent a potentially modifiable risk factor for pediatric kidney transplant complications.